Impact of relationship status on psychological parameters in adults with congenital heart disease - Stapel, Britta; Scharn, Nicole; Halling, Tim; Akkermann, Steffen; Heitland, Ivo; Westhoff-Bleck, Mechthild; Kahl, Kai G. (Frontiers in Psychiatry, 2023)
Objective: Adult congenital heart disease (ACHD) is a growing disease entity, posing questions concerning psychosocial outcomes across the lifespan. Spousal relationships were shown to benefit cardiovascular and mental health in the general population. We assessed the association of relationship status with anxiety and depression in ACHD patients and determined whether patients considered disease-related concerns potential mediators of relationship problems. Methods: N=390 ACHD patients were included. Self-report questionnaires were used to assess relationship status, ACHD-related relationship problems, socio-demographic variables, and depression and anxiety scores. Further, clinical parameters concerning the heart condition were determined. Results: N=278 (71%) patients were currently in a relationship, while N=112 (29%) were not in a relationship. Groups did not significantly differ regarding age, sex, and cardiovascular parameters. Two-way MANCOVA with relationship status and sex as independent variables, controlling for age, NYHA class, and NT-proBNP, showed an association of relationship status with depression, while sex was associated with anxiety. N=97 (25%) patients reported disease-related adverse effects on a current or prior relationship. In detail, worries about body image (N=57, 61%), own fears (N=51, 54%), problems arising from wish to have children (N=33, 35%), fears regarding a joint future (N=29, 31%), partner's fears or lack of understanding (N=28, 30%), and sexual problems (N=21, 22%) were cited. Conclusion: Relationships status was associated with depression, while sex was associated with anxiety in ACHD patients. Relationship status as well as potential relationship problems, and the importance of social support for mental and physical well-being, should be considered when treating ACHD patients.